ERAP1 association with ankylosing spondylitis is attributable to common genotypes rather than rare haplotype combinations - Roberts, A; Appleton, L; Cortes, A; Vecellio, M; Lau, J; Watts, L; Brown, M; Wordsworth, B (National Academy of Sciences, 2017)
We investigated the proposal that ankylosing spondylitis (AS) is associated with unusual ERAP1 genotypes. ERAP1 haplotypes were constructed for 213 AS cases and 46 rheumatoid arthritis controls using family data. Haplotypes were generated from five common ERAP1 single nucleotide polymorphisms (SNPs)—rs2287987 (M349V), rs30187 (K528R), rs10050860 (D575N), rs17482078 (R725Q), and rs27044 (Q730E). Haplotype frequencies were compared using Q:12 Fisher’s exact test. ERAP1 haplotypes imputed from the IGAS Immunochip study were also studied. In the family study, we identified only four common ERAP1 haplotypes (“VRNQE,” “MKDRQ,” “MRDRE,” and “MKDRE”) in both AS cases and controls apart from two rare (<0.5%) previously unreported haplotypes. There were no examples of the unusual ERAP1 haplotype combination (“*001/ *005”) previously reported by others in 53% of AS cases. As expected, K528-bearing haplotypes were increased in the AS family study (AS 43% vs. control 35%), due particularly to an increase in the MKDRQ haplotype (AS 35% vs. control 25%, P = 0.01). This trend was replicated in the imputed Immunochip data for the two K528-bearing haplotypes MKDRQ (AS 33% vs. controls 27%, P = 1.2 × 10–24) and MKDRE (AS 8% vs. controls 7%, P = 0.004). The ERAP1 association with AS is therefore predominantly attributable to common ERAP1 haplotypes and haplotype combinations.